COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA ALAM DI KINTAMANI (Studi Kasus Kawasan Batur Geopark) - Putri, Putu Pinky Ananda; Yasintha, Putu Nomy; Winaya, I Ketut (CITIZEN CHARTER; Vol 3 No 2 (2023): Administrasi Publik 2023, 2024)
Batur Geopark is attribution to an innovative approach that blends the preservation of geoscience reserves with sustainable development, under a government regulatory framework. The Batur Geopark area consists of a core village of 15 villages, and supporting villages of 33 villages. Several areas in the core village area are the center spots for tourist attractions that are frequently visited, such as Mount Batur, Black Lava, Lake Batur, Terunyan Village, Mount Batur Museum, Ulun Danu Batur Temple, hot springs, Mount Abang, Pinggan sunrise spot, and many more. Recently, there have been many developments of new tourist destinations that are increasingly attracting the attention of tourists to come to visit. Of course, the government cannot achieve this tourism development alone, but requires collaboration between the community, the private sector and the government itself. Collaboration carried out in tourism development is said to be collaborative governance.This study aims to find out how collaborative governance forms in the development of natural tourism objects in Kintamani (Case Study of the Batur Geopark Area). In this study the authors used a type of qualitative research with descriptive methods. The analysis in this study uses collaborative governance success measurement theory. The results of the research findings indicate that the collaboration between the government, the private sector, and the community has been going quite well, but there are several problems such as the domination of the government, there is still one party, namely the Batur UNESCO Global Geopark Manager who does not yet have authority, there is one party who do not have the responsibility but still able to coordinate with other parties well. As for recommendations that can be given, namely from the community, especially POKDARWIS, informing information or coordinating with the village, and parties involved in the collaboration to provide more understanding to the community outside of POKDARWIS members regarding the collaboration carried out, the positive impacts obtained, and the benefits for the community.